2019
DOI: 10.21037/atm.2019.09.68
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, immunosuppressive microenvironment and breast cancer: opportunities for cancer prevention and therapy

Abstract: Breast cancer is the most commonly diagnosed malignancy and a leading cause of cancerrelated death in women worldwide. It also exhibits pronounced racial disparities in terms of incidence and clinical outcomes. There has been a growing interest in research community to better understand the role of the microenvironment in cancer. Several lines of evidence have highlighted the significance of chronic inflammation at the local and/or systemic level in breast tumor pathobiology. Inflammation can influence breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 125 publications
(141 reference statements)
0
62
0
Order By: Relevance
“…Cancer-related inflammation leads to alteration of the tumor microenvironment and contributes to the promotion of cancer cell proliferation, invasion, and metastatic spread, and the inhibition of apoptosis and immunosuppression [16,17]. Moreover, increasing evidence suggests that inflammation plays a role in cancer development and may also be accelerated by the cancer itself due to increased catabolism and malnutrition [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related inflammation leads to alteration of the tumor microenvironment and contributes to the promotion of cancer cell proliferation, invasion, and metastatic spread, and the inhibition of apoptosis and immunosuppression [16,17]. Moreover, increasing evidence suggests that inflammation plays a role in cancer development and may also be accelerated by the cancer itself due to increased catabolism and malnutrition [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…CASP5 is an inflammatory caspase that serves a role in the immune system ( 27 – 29 ). Inflammation and cancer development are closely associated and a distinct inflammatory environment often exists within tumors ( 27 ). Multiple CASPs are abnormally expressed in GC and associated with the survival rates of GC ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the results of the present study demonstrated that a series of inflammatory proteins (such as CXCL8, IL1β and PTGS2) overexpressed by peripheral blood cells may increase systemic inflammation in female patients with CD ( 45 ). Systemic inflammation can affect tumorigenesis and progression in breast cancer by establishing a tumor immune microenvironment (TIME) ( 46 ).…”
Section: Discussionmentioning
confidence: 99%